2013
DOI: 10.1016/j.mencom.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of N-alkoxyhydrazines and N-alkoxy-N’,N’,N’-trialkylhydrazinium salts

Abstract: Mendeleev Communications N-Alkoxyhydrazines represent an interesting example of ON -N geminal systems. 1-10 Usually, N-alkoxyhydrazines are very unstable due to n N ® s* N-O(Alk) orbital interaction within the N-OAlk bond. 11 Only one compound of this type 1 is known, 11 in which the donor capacity of nitrogen is decreased owing to its participation in aziridine cycle (Scheme 1). Tetramethoxyhydrazine 2 3 easily dissociates into two dimethoxyaminyl radicals on heating since its N-N bond is weakened by n O(Me) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Pyramidal nitrogens and corresponding anomeric interactions have also been observed in the structures of a number of urea and carbamate analogues of anomeric amides ( 10 – 14 ) studied by Shtamburg and coworkers and selected structural data are presented in Table 2 [66,67,68,69]. Where substituent electronic effects are largely similar as in 11b and 13 , it can be deduced that the stronger conjugative effect of the α-nitrogen lone pair in the urea 11b, relative to the α-oxygen in the carbamate 13, results in significantly less amide resonance interaction and, hence, significant increase in pyramidality at the amide nitrogen.…”
Section: Properties Of Anomeric Amidesmentioning
confidence: 99%
“…Pyramidal nitrogens and corresponding anomeric interactions have also been observed in the structures of a number of urea and carbamate analogues of anomeric amides ( 10 – 14 ) studied by Shtamburg and coworkers and selected structural data are presented in Table 2 [66,67,68,69]. Where substituent electronic effects are largely similar as in 11b and 13 , it can be deduced that the stronger conjugative effect of the α-nitrogen lone pair in the urea 11b, relative to the α-oxygen in the carbamate 13, results in significantly less amide resonance interaction and, hence, significant increase in pyramidality at the amide nitrogen.…”
Section: Properties Of Anomeric Amidesmentioning
confidence: 99%
“…We are deeply convinced that N-hydroxyhydantoins and Nalkoxyhydantoins may bring a huge practical value in the field of pharmaceutical and medical industries as well. Our recent research in the arylglyoxals [10] has shown a completely new way to receive the N-hydroxyhydantoins [11][12][13][14] and N-alkoxyhydantoins [12][13][14][15][16][17][18][19][20][21]. We would like to continue discussing these research results in this article.…”
Section: Introductionmentioning
confidence: 89%
“…structures of a number of urea and carbamate analogues of anomeric amides (10-14) studied by Shtamburg and coworkers and selected structural data are presented in Table 2 [66][67][68][69].…”
Section: Structure N-c(o)/å (N)c=o/å θ/° C N /° τ /° Anomeric Twist 1 /°mentioning
confidence: 99%